Unveiling common pathways and potential drug targets for ulcerative colitis and IgG4-related disease through bioinformatics analysis - Liao, Quan; Zhang, Hongjian; Zhou, Fangyuan; Lin, Huasheng; Zheng, Xiongwei; Weng, Zhiyun; Li, Kaiyue; Wan, Zheng; Pan, Heng (Penerbit Universiti Kebangsaan Malaysia, 2024)
Patients with ulcerative colitis (UC) are at an increased risk of developing IgG4 related diseases (IgG4-RD). However, the molecular mechanisms are not known. This study aimed to investigate the potential molecular mechanisms and drugs to treat both UC and IgG4-RD. GSE42911 and GSE40568 datasets were intersected to generate common differentially expressed genes (DEGs). The DEGs were then subjected to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. After a protein-protein interaction network (PPI) analysis, hub genes and transcriptional regulators (TFs) were tracked. Finally, potential therapeutic drugs were predicted by the DGIDB drug database. A total of 212 common DEGs were identified in between UC and IgG4-RD. Functional enrichment revealed DEGs enriched in ‘cytoplasm’, and ‘RNA binding’. Furthermore, KEGG pathway analysis identified significant enrichment in ‘Hippo signaling’. The PPI network was enriched with 162 genes/nodes and 532 edges. Additionally, hub genes and associated with 41 TFs and 18 miRNAs were found. Finally, 16 potential drugs targeted to four hub genes were found. In summary, these findings provide novel insights into the pathophysiology of UC and IgG4-RD, highlighting potential molecular targets and drug candidates for therapeutic intervention. The identified drugs could pave the way for targeted therapies, potentially improving clinical outcomes for patients suffering from these conditions and offering a new direction for treatment strategies in both UC and IgG4-RD.